Assessment of Nurses’ Knowledge Regarding Adverse Effect Of Antihypertensive Drugs: A Cross Sectional Study - Abid Ali, Wasfi dhahir (JOURNAL OF MEDICAL AND HEALTH SCIENCE, 2023)
The current study was conducted in some hospitals in Basra, southern Iraq, on some nurses working in various departments to participate in the questionnaire, which aims to evaluate nurses’ knowledge about the adverse action of high blood pressure medications. 70 female and male nurses participated in the questionnaire to answer 20 questions. The results were 78. 49% of the nurses were sure of the answer, 20% did not know the answer, and 25.9 were not sure of their answers The total mean of score was significant (2.27),. The results conclude that knowledge of nurses regarding the adverse effects of high blood pressure medications on patients is insufficient, and nurses need to enhance scientific and practical knowledge.